The Combined Use of Platelet-Rich Plasma Clot Releasate and Allogeneic Human Umbilical Cord Mesenchymal Stem Cells Rescue Glucocorticoid-Induced Osteonecrosis of the Femoral Head - Yanxue Wang; Shuo Luan; Ze Yuan; Shaoling Wang; Shengnuo Fan; Chao Ma; Shaoling Wu (Stem Cells International)
Glucocorticoid-induced osteonecrosis of the femoral head (ONFH) is a refractory disease. The treatment options for ONFH, especially nonsurgical ones, merit further investigation. To evaluate the combinatorial therapeutic effects of platelet-rich plasma clot releasate (PRCR) and umbilical cord mesenchymal stem cells (UC-MSCs) on glucocorticoid-induced ONFH, a dexamethasone (DEX)-treated cell model and a high-dose methylprednisolone (MPS)-treated rat model were established. Cell counting kit-8 (CCK-8) assay was performed in vitro to determine the optimum dosage of PRCR for UC-MSC viability. The effects of PRCR, UC-MSCs, and PRCR + UC-MSCs on cell viability, apoptosis, migration, and differentiation capacities of DEX-treated bone marrow mesenchymal stem cells (BMSCs) and human umbilical vein endothelial cell (HUVECs) were explored via Transwell assays. Western blotting was conducted to evaluate the expression levels of RUNX2, VEGF, caspase-3, and Bcl-2 in the coculture systems. Ultrasound-guided intra-articular PRCR, UC-MSCs, and PRCR + UC-MSC injections were performed on the ONFH model rats. Microcomputed tomography, histological and immunohistochemical analyses, tartrate-resistant acid phosphatase (TRAP) staining, and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining were used to assess the therapeutic effects of PRCR and UC-MSCs on bone loss and necrosis induced by high-dose MPS. Results of this study revealed that the in vitro application of PRCR, UC-MSCs, and PRCR + UC-MSCs reversed the impaired proliferation and migration capacities and resisted apoptosis of BMSCs and HUVECs induced by DEX. Moreover, the PRCR and UC-MSC application significantly improved the alkaline phosphatase (ALP) and alizarin red (ALR) staining of BMSCs and tube formation capacity of HUVECs and promoted the protein expression of RUNX2 in BMSCs and VEGF in HUVECs. Similarly, in the ONFH rat model, the intra-articular injection of UC-MSCs and PRCR improved the subchondral bone mass parameters; promoted the expression of ALP, RUNX2, and VEGF; suppressed osteoclast overactivity; and resisted cell apoptosis. The combination of PRCR and UC-MSCs shows promising therapeutic effects in treating glucocorticoid-induced ONFH. The current study provides important information on intra-articular therapy, paving the way for the clinical management of ONFH in the future.